Cord Blood Bilirubin as a Predictor of Neonatal Hyperbilirubinemia - Saman Beg; Uzma Firdaus; Syed Manazir Ali (Acta Medica International)
Introduction: In the 1st week of life, hyperbilirubinemia is the most common clinical condition in newborns that has to be evaluated and treated. It is also a prominent cause of readmission to the hospital. Some newborns experience noticeable, potentially dangerous bilirubin levels, which can directly increase the risk of severe brain damage, despite it being a benign, postnatal, transitory phenomenon. The current investigation looked at the relationship between cord blood bilirubin levels and the predictability of pathological jaundice. Materials and Methods: Cord blood bilirubin was estimated at birth. Bilirubin estimation was done at 48 h, 72 h, and 5–7 days of life using a trans-bilirubinometer. The study was approved by the Institutional Ethical Committee. Results: Significant hyperbilirubinemia was found in 3.7% of the neonates. A statistically significant correlation was found between cord blood bilirubin and the development of significant hyperbilirubinemia at 48 h of life. Gender, gestational age, birth weight, and use of Oxytocin have no correlation with cord bilirubin or the subsequent development of jaundice. A cord blood value of >2 mg/dL has a high negative predictive value (98%), sensitivity (83%), specificity (41%), and positive predictive value (5.3%) in predicting the future development of future pathological jaundice. Conclusions: A high negative predictive value in our study suggests that healthy term babies with cord bilirubin ≤2 mg/dL can be discharged early with assurance to parents. Babies with cord blood bilirubin >2 mg/dL should be followed more frequently.